2019
DOI: 10.1080/14783363.2019.1625266
|View full text |Cite
|
Sign up to set email alerts
|

Why firms lose their ISO 9001 certification: Evidence from Portugal

Abstract: More than one million certified companies must choose, every three years, whether to renew or to withdraw from ISO 9001 certification. This paper investigates whether ISO 9001 decertification decision is driven by economic motivations. Using standard event-study methods, the paper looks into this question by comparing the abnormal performance of a sample of Portuguese firms that lose their certification with that of similar, non-event, firms. The paper finds no statistically significant differences in the econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 38 publications
2
37
0
2
Order By: Relevance
“…Prior studies that discussed the performance of quality management practices (e.g., TQM or quality certification) were inconclusive. One stream of the studies considered that quality management practices can improve the sales or profit [4,5,7], while some research showed that quality management practices may bring large costs [18] and the effects will not last for a long time [19]. We provide two explanations for these contradictory results.…”
Section: Theory and Hypothesismentioning
confidence: 89%
See 3 more Smart Citations
“…Prior studies that discussed the performance of quality management practices (e.g., TQM or quality certification) were inconclusive. One stream of the studies considered that quality management practices can improve the sales or profit [4,5,7], while some research showed that quality management practices may bring large costs [18] and the effects will not last for a long time [19]. We provide two explanations for these contradictory results.…”
Section: Theory and Hypothesismentioning
confidence: 89%
“…For example, the ISO 9001 standards require detailed documentation of production processes, and maintaining this certification costs substantial resources. Nearly 60,000 firms purposely lose ISO 9001 certifications each year to save the registration and implementation costs [18]. From this perspective, firms may not obtain the expected financial benefits if their revenue cannot offset the influence of the cost of quality certification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Los motivos de que la ISO 9001 haya dejado atrás la fase de crecimiento puede estar en el abandono de las certificaciones, pero también en las barreras de entrada o en la reducción del atractivo para las restantes empresas no certificadas (Zimon y Dellana, 2019;Simon y Kafel, 2018;Cândido et al, 2019;Kafel y Simon, 2017;Sansalvador y Brotins, 2015). Profundizando en ese ámbito, otros trabajos analizan el impacto que tienen sobre las empresas la cancelación de esta certificación (Alič, 2014;Cândido et al 2016).…”
Section: Certificaciones Iso 9001 Y "Q De Calidad" En El Sector Alojamiento Y Restauración Españolunclassified